TEACHER INNOVATION THROUGH WORK MOTIVATION AND TRANSFORMATIONAL LEADERSHIP IN PUBLIC SENIOR HIGH SCHOOLS: PATH ANALYSIS - Memet Casmat; Soewarto Hardhienata; Suhendra (Antis Publisher, 2026)
Objective: This study aims to analyze the direct and indirect effects of transformational leadership (X1), the effectiveness of information and communication technology/ICT utilization (X2), self-efficacy (X3), and work motivation (X4) on teacher innovativeness (Y) in State Senior High Schools (SMA Negeri) in Bogor Regency through a path analysis approach. Method: This study uses an empirical quantitative approach by applying path analysis and SITOREM analysis to a sample of 218 State Senior High School teachers in Bogor Regency with a total of 153 respondents. Data were collected using a validated Likert scale instrument and analyzed using the SPSS program. Results: The results showed that the four independent variables had a positive and significant direct effect on teacher innovativeness. The largest direct path coefficient was found in the effectiveness of ICT utilization (β = 0.425), followed by transformational leadership (β = 0.216), work motivation (β = 0.163), and self-efficacy (β = 0.156). Work motivation has been shown to significantly mediate the influence of each exogenous variable on teacher innovation, as evidenced by the Sobel test with a Z-value of >1.97 across all tested paths. Novelty: The novelty of this study lies in the integration of SITOREM analysis with path analysis, enabling the study not only to identify causal relationships between variables but also to prioritize indicators that need immediate improvement and indicators that need to be maintained or developed. This approach produces an operational strategy for improving teacher innovation that can be directly implemented by school administrators.